SESAM combined Kerr lens mode locked Yb:CALGO laser pumped by a 1.2 W single mode fiber coupled laser diode. (22nd March 2017) - Wang, Yanbiao; Wang, Sha; Feng, Guoying; Zhou, Shouhuan
Abstract: In this letter, we present a passively mode locked Yb:CALGO oscillator pumped by a 1.2 W single mode fiber coupled laser diode. In semiconductor saturable absorber mirror (SESAM) mode locking regime, maximum output power of 385 mW with a laser slope efficiency of 40% has been achieved. The pulse duration of the mode locked pulse is 630 fs, and the full width at half maximum (FWHM) of the spectrum is measured as only about 2.7 nm. By finely tuning the laser cavity, the laser starts to work in the SESAM combined Kerr lens mode locking regime. Compared with SESAM mode locking only, a maximum reduction factor of 6.33 in pulse duration has been achieved by the combined mode locking mechanism. By optimizing the group delay dispersion (GDD) inside the laser cavity, the shortest pulse duration of 70 fs and FWHM of 19.8 nm at output power of 210 mW has been realized.